Pengenalan SDGs Bagi Siswa Sekolah Agama Berasrma Penuh Maahad Ahmadi Negeri Sembilan Malaysia untuk Membangun Pemuda Kritis dan Agen Perubahan - Simamora, Beltahmamero; Rahman, Fauziah; Ritonga, Syafruddin (Pelita Masyarakat, 2025)
This research aims to increase students' understanding and awareness of the importance of the Sustainable Development Goals (SDGs) through socialization activities carried out at the Maahad Ahmadi Negeri Sembilan Boarding Boarding School (SABP MANS), Youth in Malaysia have great potential as agents of change in sustainable development, but the low SDGs literacy among students, especially in faith-based schools, is still a challenge. This activity uses the method of lectures and participatory discussions to instill critical values and social responsibility. A total of 30 students participated in the training and were evaluated through questionnaires to measure their understanding and commitment to real action. The results of the analysis showed that participants had high enthusiasm and showed increased understanding and desire to engage in various sustainability activities. The majority of students show interest in SDGs education, environmental issues, and social engagement. This research recommends the integration of SDGs education into the school curriculum and the continuous expansion of similar activities to shape the younger generation as critical thinkers and change-makers in the future.